CIVIL ENGINEERING MATERIALS -A REVIEW (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Civil Engineering based on the many characteristically, diversified public works based projects depends on the design, inspection, management and maintenance criteria’s or properties. These projects starts from the house hold applications to high rise buildings and from rail road manufacturing to the dam construction or giant plant infrastructures. At the core of this branch nothing but the civil engineering, materials and the methods of these materials can satisfy the need of above mentioned characteristics. Selection of the right material for the specific use and also appropriate method for material selections are the key factors for the construction of any structure. This review paper is based on the various types of materials used in the civil engineering and the prons and cons of these materials.